Like a Fish Outside the Sea: An Ethnographic Exploration of Why and How Young Lebanese from El-Mina Migrate to Europe - Studer, Lea Farida (AUC Knowledge Fountain, 2025)
Following the Thawra in 2019, Lebanon’s initial optimism for political change has given way to a harsh reality. The country, troubled by hyperinflation, deteriorating state services, and worsening living conditions, coupled with corruption and sectarianism, is seeing an increasing number of Lebanese seeking alternative futures abroad, including in Europe. Be it via regular or irregular pathways, young Lebanese adults have been leaving the country, their families, their friends – their homes. This ethnographic Master’s thesis, which was conducted during the Summer of 2023 in El-Mina, a port city in northern Lebanon, delves into the aspirations and capabilities that drive young Lebanese to migrate to Europe. Through fifteen semi-structured interviews, group discussions, and participant observation, the study examines the origins and the development of migration experiences in the context of El-Mina. It critically examines the resources crucial to migration decisions and the diverse actors and regulations involved in facilitating or constraining migration pathways. By illuminating these dynamics, this thesis offers a nuanced understanding of how youth from a small port community navigate and overcome emigration challenges. The findings reveal that emigration decisions are driven by both intrinsic and instrumental aspirations and that there is never just one single motivation. Individuals with lower economic, social, and human capital were found to prioritize intrinsic aspirations, while those with greater capital focus more on instrumental goals, often having a more concrete plan for future accomplishments. Thereby, emotions and mental health proved to be central dimensions that should be given greater consideration in future research to enable a more comprehensive understanding of aspirations. The thesis further illustrates that migration methods differ according to capital, with individuals possessing more capital typically emigrating through regular channels. In comparison, those with less capital often employ irregular means to reach Europe. However, people without access to (financial) capital are unable to emigrate. The interviews highlight the complexity of emigration processes shaped by the Lebanese context, capital composition, and migration governance, and portray migrants as active actors rather than passive victims. While the macro-level context influences aspirations and capabilities in general, it is the individual situation that determines the composition and importance of different aspirations and dictates individual access to capital and resources, thus shaping the mode of migration. Thereby, this study contributes to filling gaps in the literature on the emigration trends of Lebanese youth and the impact of emigration policies, in the example of El-Mina.